Vitamin D receptor interacts with NLRP3 to restrict the allergic response. (9th September 2018) - Huang, H.; Hong, J.‐Y.; Wu, Y.‐J.; Wang, E.‐Y.; Liu, Z.‐Q.; Cheng, B.‐H.; Mei, L.; Liu, Z.‐G.; Yang, P.‐C.; Zheng, P.‐Y.
Summary: Vitamin D receptor (VDR) mediates various biochemical activities between the cytoplasm and the nucleus in the cell. The nucleotide‐binding, oligomerization domain (NOD)‐like receptor family, pyrin domain containing 3 (NLRP3) protein is involved in the T helper type 2 (Th2) response. This study tests a hypothesis that VDR interacts with NLRP3 to restrict the Th2‐biased response. In this study, VDR –/– mice and WT (WT) mice were used. Th2 cell differentiation between VDR –/– mice and WT mice was observed. We observed that CD4 + T cell activation was higher in VDR –/– mice. The VDR –/– CD4 + T cells were prone to Th2 polarization. VDR –/– mice produced more immunoglobulin (Ig)E. VDR bound NLRP3 to prevent Th2 differentiation by restricting IL4 gene transcription. Th2 biased inflammation spontaneously developed in the intestine of VDR –/– mice. In conclusion, VDR binds NLRP3 to restrict IL4 gene transcription and prevent biased Th2 polarization. Abstract : VDR expression is lower in CD4+ T cells of FA patients; VDR is negatively correlated with Th2 cytokines in CD4+ T cells of FA patients